Does hormone replacement therapy impact implant osseointegration in females- A systematic review and meta-analysis - Tushar Sinha; Jayant Prakash; Mahesh Suganna Golgeri; Daginakatti Shambhulingappa Aruna; Bukanakere Sangappa Sunila; Ganiga Channaiah Shivakumar; Marco Cicciù; Giuseppe Minervini (Elsevier, 2024)
Background: This review aimed to comprehensively investigate the impact of Hormone Replacement Therapy (HRT) on implant osseointegration and bone loss. The study considered factors such as HRT type, osteoporosis, smoking, and diabetes mellitus, and analysed the available literature to provide insights into the association between HRT and implant outcomes. Methods: Multiple databases were utilized, and studies with diverse designs and methodologies were included that examined the relationship between HRT and implant osseointegration. The selected studies were analyzed and relevant data on implant success rates, bone loss, and other correlations was extracted. Results: The review findings indicate that HRT has a detrimental impact on implant osseointegration, as evidenced by lower implant success rates and increased bone loss in HRT-treated individuals. The odds ratio analysis further strengthens this association, with significant values of 0.59 (95% CI: 0.50-0.70) and 0.64 (95% CI: 0.54-0.76), indicating a higher likelihood of implant failure in HRT-treated patients., highlighting the need for caution when considering HRT as a treatment option in patients undergoing implant procedures. Smoking and diabetes mellitus were also found to significantly affect implant outcomes, emphasizing the importance of addressing these factors in patient management. Conclusion: The assessments demonstrate that HRT adversely affects implant osseointegration and increases bone loss. The results suggest the importance of considering the potential negative impact of HRT on implant outcomes and the need for thorough patient evaluation and management. Further research is warranted to explore the underlying mechanisms, assess the impact of specific HRT types and dosages, and evaluate preventive strategies to mitigate the detrimental effects of HRT on implant success.